2022
DOI: 10.1007/s00161-021-01072-6
|View full text |Cite
|
Sign up to set email alerts
|

Extended micropolar approach within the framework of 3M theories and variations thereof

Abstract: As part of his groundbreaking work on generalized continuum mechanics, Eringen proposed what he called 3M theories, namely the concept of micromorphic, microstretch, and micropolar materials modeling. The micromorphic approach provides the most general framework for a continuum with translational and (internal) rotational degrees of freedom (DOF), whilst the rotational DOFs of micromorphic and micropolar continua are subjected to more and more constraints. More recently, an “extended” micropolar theory has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…This case corresponds to symmetric material particles such as spheres. Dynamic properties introduced through two micro-inertia tensors could be taken into account considering material symmetry as in Eremeyev and Konopińska-Zmysłowska (2020); see also Vilchevskaya et al (2022), where other references on micro-inertia tensors could be found. Derived here formulae for the micro-inertia tensors complete the description by Eremeyev (2019) of a network undergoing large deformations within micro-polar elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…This case corresponds to symmetric material particles such as spheres. Dynamic properties introduced through two micro-inertia tensors could be taken into account considering material symmetry as in Eremeyev and Konopińska-Zmysłowska (2020); see also Vilchevskaya et al (2022), where other references on micro-inertia tensors could be found. Derived here formulae for the micro-inertia tensors complete the description by Eremeyev (2019) of a network undergoing large deformations within micro-polar elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Definition (1.8) slightly deviates from the definition of the inertia tensor commonly used in classical mechanics [17]. However, the two formulations can be transformed into each other, as described in [36]. By the use of the inertia tensor i and gyration tensor G, the spin inertia per unit mass σ [6] is defined:…”
Section: Micro-continuum Approachmentioning
confidence: 99%
“…It characterizes the change in time of a particle's spin angular momentum (cf. [36]). The field quantities introduced in this section are used to formulate the governing balance and constitutive equations of a micromorphic fluid below.…”
Section: Micro-continuum Approachmentioning
confidence: 99%
“…In Ref. [60], authors present an extended micropolar approach within framework of Eringen's micropolar, microstretch, and micromorphic theories and some variations. In Ref.…”
Section: Nonclassical Micropolar Theories Of [25–27 60–62] and Compar...mentioning
confidence: 99%